COOLING STRUCTURE OF MOTOR - SEO NOBUHIDE; HIRANO TAKUO; YONEMORI TAKASHI; TANEHIRA TAKAFUMI (2015)
PROBLEM TO BE SOLVED: To realize a cooling structure of a motor which achieves energy saving and high efficiency.SOLUTION: A cooling structure of a motor includes: a sealed case in which a refrigerant is enclosed; and a vibration transmission means which transmits electromagnetic vibration of a stator to the liquid refrigerant. The refrigerant is subject to heat from a coil of the stator to be evaporated, radiates heat at a predetermined heat radiation part to be liquefied, and circulates in the sealed case. 【課題】本発明は、省エネで、かつ、効率のよいモータの冷却構造を実現することを課題とする。【解決手段】冷媒が封入された密閉ケースと、液体状態の冷媒にステータの電磁振動を伝達する振動伝達手段と、を備え、冷媒は、ステータのコイルからの熱を受けて気化し、所定の放熱部で放熱して液化し、密閉ケース内を循環することを特徴とする。【選択図】図１